Who Gets Stitches? The Effects of Rewarding Whistleblowers and Protecting Their Identity on Subsequent Willingness to Work With Others - Sommerfeldt, Ryan D. (Contemporary Accounting Research, 2026)
ABSTRACT Companies are strongly encouraged to implement whistleblowing programs to help detect and deter misconduct in organizations, but whistleblowers often face ostracism, as their coworkers are less willing to work with them (the whistleblower effect). Rewarding the whistleblower and protecting the whistleblower's identity are two highly recommended features of whistleblowing programs that aim to encourage reporting. Across two experiments, I examine the spillover effects of these whistleblowing program features on how willing employees are to work with their coworkers after reporting occurs. I find that providing a reward to the whistleblower exacerbates the whistleblower effect, leading employees to work even less with the whistleblower (the reward effect). I also find that protecting the whistleblower's identity removes the reward effect but does not remove the whistleblower effect. Instead, the whistleblower effect is extended to neutral coworkers. As a result, when employees do not know the identity of the whistleblower, they view their coworkers less as separate individuals and are less willing to work with everyone in their group.